Longitudinal Investigation of the Biomarkers of Iodine Status in Pregnant and Post-partum Women in Perth - Jorgensen, Anita Michelle (Curtin University, 2018)
This longitudinal study found no significant change in iodine status, as measured by urinary iodine excretion, with advancing gestation in a cohort of Perth women (n=61). In addition, these women had adequate iodine intake despite the non-universal use of iodine supplementation. These results challenge the NHMRC recommendation for all Perth pregnant and breastfeeding women to use daily iodine-containing supplements. However, future research with larger and more representative samples should be conducted to validate these outcomes.